2014
DOI: 10.1016/j.jacc.2014.09.072
|View full text |Cite
|
Sign up to set email alerts
|

The Incremental Risk of Noncardiac Surgery on Adverse Cardiac Events Following Coronary Stenting

Abstract: The incremental risk of noncardiac surgery on adverse cardiac events among post-stent patients is highest in the initial 6 months following stent implantation and stabilizes at 1.0% after 6 months. Elective, high-risk, inpatient surgery, and patients with DES may benefit most from delay from a 6-month delay after stent placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 40 publications
2
52
0
Order By: Relevance
“…[101][102][103]149 Data from more recent large observational studies suggest that the time frame of increased risk of stent thrombosis is on the order of 6 months, irrespective of stent type (BMS or DES) . [151][152][153] In a large cohort of patients from the Veterans Health Administration hospitals, the increased risk of surgery for the 6 months after stent placement was most pronounced in those patients in whom the indication for PCI was an MI . 146 An additional consideration, irrespective of the timing of surgery, is that surgery is associated with proinflammatory and prothrombotic effects that may increase the risk of coronary thrombosis at the level of the stented vascular segment as well as throughout the coronary vasculature .…”
Section: Iii: Harm B-nrmentioning
confidence: 99%
“…[101][102][103]149 Data from more recent large observational studies suggest that the time frame of increased risk of stent thrombosis is on the order of 6 months, irrespective of stent type (BMS or DES) . [151][152][153] In a large cohort of patients from the Veterans Health Administration hospitals, the increased risk of surgery for the 6 months after stent placement was most pronounced in those patients in whom the indication for PCI was an MI . 146 An additional consideration, irrespective of the timing of surgery, is that surgery is associated with proinflammatory and prothrombotic effects that may increase the risk of coronary thrombosis at the level of the stented vascular segment as well as throughout the coronary vasculature .…”
Section: Iii: Harm B-nrmentioning
confidence: 99%
“…1,[16][17][18][19] More recently, however, Holcomb and colleagues demonstrated that the incremental risk of cardiac complications significantly decreases when surgery is performed more than 6 months following coronary stenting: the incremental risk of cardiac complications stabilizes at 1% beyond 6 months following coronary stenting. 20 Although NSQIP excludes those with prior percutaneous coronary intervention within 6 months of hepatectomy, we still found that those with history prior PCI (>6 months before the liver resection) had a cardiac complication rate of 6.4% as well as a three-fold increase risk of cardiac arrest. One can infer that underlying coronary disease, the complexity of liver surgery, and a fluid restrictive strategy maintaining a low CVP and perhaps necessitating vasopressors are all synergistic drivers of major adverse cardiac complications in patients undergoing major liver resection.…”
Section: Discussionmentioning
confidence: 72%
“…A key predictor of major adverse cardiac and cerebrovascular events (MACCE) appears to be the time elapsed between coronary stent implantation and surgery. In a linked administrative database study involving 20 590 patients with coronary stents and 41 180 control patients without stents who had non-cardiac surgery, the incidence of MACCE was highest in the initial 6 weeks after surgery but remained significantly higher than in the control group until 6 months postsurgery 42. These results are expanded by those of a Danish cohort of 22 590 patients with drug-eluting coronary stents in which 4303 patients with surgery within 1 year were frequency matched by surgery type with 20 232 controls.…”
Section: Introductionmentioning
confidence: 97%